The Role of Psilocybin-Assisted Psychotherapy to Support Patients With Cancer: A Critical Scoping Review of the Research. (September 2022) - Lehto, Rebecca H.; Miller, Megan; Sender, Jessica
Treatments for addressing psychiatric mental health issues in vulnerable patients with cancer are established. Yet, many patients persist with unrelenting psychological difficulties despite intervention. There is growing interest in the role of psilocybin-assisted psychotherapy for managing treatment-resistant mental health challenges in patients with cancer. Psilocybin is a naturally occurring compound derived from certain mushroom species that can induce entheogenic experiences or an altered state of consciousness. Reed's Self-Transcendence Theory provides a holistic lens to examine existential concerns and mental health in individuals who perceive their illness as potentially life threatening, such as those with cancer. This scoping literature review used Arksey and O'Malley's template to evaluate research examining psilocybin-assisted psychotherapy for patients with cancer. Eight articles met inclusion/exclusion criteria (four quantitative, two mixed methods, and two qualitative). Review findings indicated that the majority of patient experiences were positive, centering on themes of death acceptance, reflection, and broadened spirituality. Although psilocybin-assisted psychotherapy is in early stages of clinical testing, it thus shows promise for carefully screened patients with cancer who have persistent existential suffering. It will be critical for investigators to tailor this emerging intervention to select patients and for clinicians to be engaged in assessment of outcomes and efficacy.